2021
DOI: 10.1038/s41392-021-00650-z
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasomes as therapeutic targets in human diseases

Abstract: Inflammasomes are protein complexes of the innate immune system that initiate inflammation in response to either exogenous pathogens or endogenous danger signals. Inflammasome multiprotein complexes are composed of three parts: a sensor protein, an adaptor, and pro-caspase-1. Activation of the inflammasome leads to the activation of caspase-1, which cleaves pro-inflammatory cytokines such as IL-1β and IL-18, leading to pyroptosis. Effectors of the inflammasome not only provide protection against infectious pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
91
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(95 citation statements)
references
References 170 publications
1
91
0
3
Order By: Relevance
“…Diabetes and its complications activate NLRP3 inflammasome through hyperglycemia, hypercholesterolemia, and hyperuricemia, resulting in a rise of IL-1β and IL-18 levels and inducing inflammatory response (Schroder et al, 2010). The current study revealed that reducing NLRP3 inflammasome activation can prevent and reduce diabetic complications (Ashrafizadeh et al, 2021;Li et al, 2021). As an upstream regulator of NLRP3 inflammasome, lncRNA can exert control over diabetes and its complications (Li et al, 2017b).…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Diabetes and its complications activate NLRP3 inflammasome through hyperglycemia, hypercholesterolemia, and hyperuricemia, resulting in a rise of IL-1β and IL-18 levels and inducing inflammatory response (Schroder et al, 2010). The current study revealed that reducing NLRP3 inflammasome activation can prevent and reduce diabetic complications (Ashrafizadeh et al, 2021;Li et al, 2021). As an upstream regulator of NLRP3 inflammasome, lncRNA can exert control over diabetes and its complications (Li et al, 2017b).…”
Section: Introductionmentioning
confidence: 71%
“…Increasing evidence demonstrates that NLRP3 inflammasome is implicated in developing diabetes and associated complications ( Schroder et al, 2010 ; Wada and Makino, 2016 ; Tang and Yiu, 2020 ; Li et al, 2021 ). Diabetes and its complications activate NLRP3 inflammasome through hyperglycemia, hypercholesterolemia, and hyperuricemia, resulting in a rise of IL-1β and IL-18 levels and inducing inflammatory response ( Schroder et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammasomes are cytosolic multiprotein complexes that typically have three main components: a cytosolic pattern-recognition receptor, the enzyme caspase-1, and an adaptors ( 30 ). The activation of caspase-1 cleaved the inactive pro-IL-1β and pro-IL-18 into mature cytokines and induce a pro-inflammatory cell death, pyroptosis ( 5 , 31 ). An increasing number of evidence has shown that Z-VAD-FMK or AC-YVAD-CMK, caspase-1 inhibitors, could reduce inflammasome activation-mediated inflammatory response and neuronal cell death after stroke ( 32 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammasome complexes are a part of the innate immune system initiating inflammation. Their activation leads to the activation of caspase-1, which is responsible for the cleavage and subsequent activation of proinflammatory cytokines, such as IL-1β [56]. Its expression has been seen in the primary cells of myeloid and lymphoid origin as well as bone marrow and B cells and to be upregulated in chicken macrophages under inflammatory states [57,58].…”
Section: Discussionmentioning
confidence: 99%